2015
DOI: 10.1126/scisignal.2005659
|View full text |Cite
|
Sign up to set email alerts
|

Localized TRPA1 channel Ca 2+ signals stimulated by reactive oxygen species promote cerebral artery dilation

Abstract: Reactive oxygen species (ROS) can have divergent effects in cerebral and peripheral circulations. We found that Ca2+-permeable transient receptor potential ankyrin 1 (TRPA1) channels were present and colocalized with NADPH (reduced form of nicotinamide adenine dinucleotide phosphate) oxidase 2 (NOX2), a major source of ROS, in the endothelium of cerebral arteries but not in other vascular beds. We recorded and characterized ROS-triggered Ca2+ signals representing Ca2+ influx through single TRPA1 channels, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
196
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(207 citation statements)
references
References 39 publications
10
196
1
Order By: Relevance
“…Previous studies of endothelial Ca 2+ signals have demonstrated that localized Ca 2+ signals predominantly activate IK and SK channels to cause vasodilation in small systemic arteries including mesenteric, cremaster, and cerebral arteries 1, 2, 3, 4, 56. In small PAs, TRPV4 sparklets preferentially activated eNOS to cause vasodilation.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies of endothelial Ca 2+ signals have demonstrated that localized Ca 2+ signals predominantly activate IK and SK channels to cause vasodilation in small systemic arteries including mesenteric, cremaster, and cerebral arteries 1, 2, 3, 4, 56. In small PAs, TRPV4 sparklets preferentially activated eNOS to cause vasodilation.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that oxidative degradation of membrane lipids is increased in the vascular wall during hypertension and TRPA1 activity is enhanced. This augmented activity is protective against hemorrhagic stroke associated with hypertension [176]. TRPA1 is also activated by ω-3 PUFAs such as DHA which could partially explain the important role of dietary assumption of these fatty acid in cardio-and cerebrovascular disease management.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Similar to Ca 2+ pulsars, Ca 2+ wavelets have been reported in skeletal muscle arteries [16]. More recently, a spatially restricted Ca 2+ influx through plasma membrane ion channels, TRPV4-and TRPA1-sparklets, has been reported with an elegant demonstration of the requirement of intracellular scaffolding for cellular function [12,14,16]. These investigations emphasize the need for a better understanding of the regulatory mechanisms of confined Ca 2+ dynamics.…”
Section: Introductionmentioning
confidence: 92%
“…Thus, localized Ca 2+ events such as Ca 2+ pulsars, Ca 2+ wavelets, TRPV4-and TRPA1-sparklets have recently been characterized and are suggested to regulate vascular tone [12][13][14][15][16]. Early work on Ca 2+ pulsars reported a spontaneous Ca 2+ release from IP 3 -sensitive stores within myoendothelial projections (MEP) in mesenteric resistance arteries [15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation